2001
DOI: 10.1093/cje/25.6.765
|View full text |Cite
|
Sign up to set email alerts
|

Institutional individualism and institutional change: the search for a middle way mode of explanation

Abstract: After noting the lack of enthusiasm of several well-known scholars concerning the adoption of both methodological holism and methodological individualism in its several versions, the present article shows that institutional individualism is a different mode of explanation from both of these and also that it is not the same thing as the so-called Popperian program of situational analysis. Institutional individualism is a mode of explanation that yields non-systemic and non-reductionist explanations at the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 61 publications
0
5
0
7
Order By: Relevance
“…Since the norms, inter alia, can be defined as a framework within which individuals interpret the current situation and recognise their responsibility (Fine, 2001, p. 140) it can be concluded that, instead of homo oeconomicus, a research focus of institutional indvidiualism diverts to homo institutius. Accordingly, one must proceed from three basic assumptions, or the three basic rules of institutional individualism (Toboso, 2001, p. 773).…”
Section: Institutional Individualismmentioning
confidence: 99%
“…Since the norms, inter alia, can be defined as a framework within which individuals interpret the current situation and recognise their responsibility (Fine, 2001, p. 140) it can be concluded that, instead of homo oeconomicus, a research focus of institutional indvidiualism diverts to homo institutius. Accordingly, one must proceed from three basic assumptions, or the three basic rules of institutional individualism (Toboso, 2001, p. 773).…”
Section: Institutional Individualismmentioning
confidence: 99%
“…31-36). No obstante, el individualismo del nuevo institucionalismo avanzó hacia un individualismo con trasfondo social a través de la propuesta de Toboso (2001) del "individualismo institucional", que se adecua correctamente a buena parte de la NEI.…”
Section: La Nueva Economía Institucionalunclassified
“…En este sentido, la propuesta de la NEI ha incorporado y desarrollado argumentos que encajan con mayor dificultad en los fundamentos neoclásicos, como en el caso del individualismo institucional (Toboso, 2001), de las creencias y modelos mentales de los individuos (North, 2005), de la importancia de los factores distributivos y de conflicto social (Toboso y Compés, 2003) o del papel del poder de coerción (Nye, 1997;Toboso, 1997). Todo ello evidencia una NEI muy activa y en continuo desarrollo y diálogo con la corriente principal, pero también con la tradición institucionalista.…”
Section: "Viejo Institucionalismo" (Vi)unclassified
“…No obstante, el individualismo del nuevo institucionalismo avanzó hacia un individualismo con trasfondo social en el sentido de lo que expresó Sáez Pérez (1997: 126-127). De hecho, la propuesta de Toboso (2001) del individualismo institucional se adecua correctamente a buena parte de la NEI. importancia del paso del tiempo y al rechazar el modelo de elección basado en racionalidad perfecta, incorporando las limitadas capacidades cognitivas del individuo a través de conceptos como la racionalidad limitada y las creencias.…”
Section: Fundamentos Teóricos: Costes De Transacción E Institucionesunclassified
“…De este modo, los enfoques institucionalistas, con North (2005) como máximo exponente, han acabado modificando aspectos del núcleo duro del marco teórico de la economía neoclásica precoaseana y de la propia teoría de la elección racional. En este sentido, la propuesta institucionalista ha incorporado y desarrollado argumentos que no encajan en la ortodoxia neoclásica, como en el caso del individualismo institucional (Toboso, 2001), de la racionalidad limitada y las creencias (Caballero y Kingston, 2005b), de la influencia institucional de la historia (Caballero, 2004) o del papel del poder de coerción (Toboso, 1997). La conclusión es que la agenda de trabajo del enfoque institucional ha desarrollado fundamentos teóricos que permiten una comprensión multidisciplinar más amplia de la ciencia regional, del espacio y de la propia identidad política.…”
Section: Introducción*unclassified